IMPORTANT ECOLINGUISTIC INSIGHTS INTO THE RUSSIAN LINGUISTIC LANDSCAPE AND DISCOURSE. - Lisek, Grzegorz; Kowalonek-Janczarek, Monika (Croatica et Slavica Iadertina, 2025)
The article reviews Martin Henzelmann's 2024 monograph, which investigates ecological discourse in Russia through the lens of language, law, and visual practices in public spaces, particularly in protected natural areas. The study shifts the focus of Linguistic/Semiotic Landscape research from urban centers to rural settings, emphasizing the role of visual communicative artifacts like signs and maps in conveying ecological governance. Key findings include the significance of typographic design, the functional use of color in signage, and the impact of lexical anchors on discourse. The work is noted for its methodological rigor and theoretical contributions, particularly in integrating various linguistic approaches to enhance understanding of ecological communication in non-urban contexts.